Depressive disorder at the household level: prevalence and correlates of depressive symptoms among household members - Kondwani Mpinga; Temusa Rukundo; Owen Mwale; Myrrah Kamwiyo; Limbani Thengo; Todd Ruderman; Beatrice Matanje; Fabien Munyaneza; Emilia Connolly; Kazione Kulisewa; Michael Udedi; Chiyembekezo Kachimanga; et al. (Taylor & Francis Group, 2023)
Background Globally, an estimated five percent of adults have major depressive disorder. However, little is known about the relationship between these individuals' depressive symptoms and their household members' mental health and well-being. Objectives We aimed to investigate the prevalence and predictors of depressive symptoms among adult household members of patients living with major depressive disorder in Neno District, Malawi. Methods As part of a cluster randomized controlled trial providing depression care to adults with major depressive disorder, we conducted surveys with patients' household members (n = 236) and inquired about their overall health, depressive symptoms, disability, and social support. We calculated prevalence rates of depressive disorder and conducted multivariable linear regression and multivariable logistic regression analyses to assess correlates of depressive symptom severity and predictors of having depressive disorder (PHQ-9), respectively, among household members. Results We observed that roughly one in five household members (19%) screened positive for a depressive disorder (PHQ-9 > 9). More than half of household members endorsed six or more of the nine symptoms, with 68% reporting feeling 'down, depressed, or hopeless' in the prior two weeks. Elevated depression symptom severity was associated with greater disability (β = 0.17, p < 0.001), less social support (β = −0.04, p = 0.016), and lower self-reported overall health (β = 0.54, p = 0.001). Having depressive disorder was also associated with greater disability (adjusted Odds Ratio [aOR] = 1.12, p = 0.001) and less social support (aOR = 0.97, p = 0.024). Conclusions In the Malawian context, we find that depressive disorder and depression symptoms are shared attributes among household members. This has implications for both screening and treatment, and it suggests that mental health should be approached from the vantage point of the broader social ecology of the household and family unit. Trial Registration ClinicalTrials.gov (NCT04777006) - March 2, 2021.